Flip Chip integration of ultra-thinned dies in low-cost flexible printed electronics; the effects of die thickness, encapsulation and conductive adhesives. (August 2021) - Malik, Muhammad Hassan; Grosso, Giovanna; Zangl, Hubert; Binder, Alfred; Roshanghias, Ali
Abstract: As the demand for flexible hybrid electronics has increased extensively e.g. for the internet of things (IoT), electronic skin and wearables applications, the implementation of devices based on low-cost materials such as PET, paper, and unpackaged bare dies have become crucial for economical mass production. To facilitate flexibility for instance in wearables, the rigid silicon-based components are also deemed to become ultra-thin, which raises major challenges in terms of handling and reliable integration. In this paper, the hybrid integration of ultra-thin dies on PET and paper-based printed substrates is investigated. Silicon dies with different thicknesses from 10 to 50 μm with an internal daisy-chain structure were made and flip-chip bonded to screen-printed substrates. The bonding was conducted by using two types of anisotropic conductive adhesives, i.e. anisotropic conductive films (ACF) and anisotropic conductive paste (ACP). The effect of die encapsulation on the reliability of the assembly was also assessed by employing a protective foil. For reliability analysis, a cyclic bending test was carried out to identify the failure cycle. The successful integration of ultra-thin chip on the low-cost printed flexible substrate was obtained by optimizing the bonding parameters with both ACF and ACP. It was revealed that in flexible hybrid electronics; the thinner the die, the higher is the reliability, as the thinner dies promise superior flexibility, and can withstand higher bending stresses. Moreover, it was found that encapsulation of the thin die in a foil dramatically increases the long-term reliability of the bonded chip. Highlights: Ultra-thinned dies in a variety of thicknesses down to 10 μm were bonded to paper and PET substrates. The electrical performance of the joints was examined via cyclic bend testing. The bending radius of the dies was also computed via FEM simulation. Dies with lower thicknesses withstood higher bending cycles due to the lower stiffness. By encapsulating the dies in a foil, the reliability and averages failure cycles increased.